2017
DOI: 10.1007/s11250-017-1303-y
|View full text |Cite
|
Sign up to set email alerts
|

Concentrate supplementations of grazing pregnant Kalahari Red goats: Effects on pregnancy variables, reproductive performance, birth types and weight of kids

Abstract: A study was conducted for 22 weeks to determine the effects of concentrate supplementations at three crude protein (CP) levels, i.e. low protein diet-LPD 12.42% CP (124.93 g day); medium protein diet-MPD 14.18% CP (145.87 g day) and high protein diet-HPD 16.35% CP (168.19 g day) on some pregnancy variables, reproductive performance, birth types and weight of kids kidded by pregnant Kalahari Red goats grazed on Chloris gayana. Thirty-three matured Kalahari Red goats of first parity within age range of 2 to 2/ y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Ovulation rate sets the upper limit to fecundity (the number of kids born per pregnant doe). Goats are prolific breeders and high rates of fecundity have been reported in numerous countries and breeds, including in Kalahari Red, 1.6 kids/ doe (Oderinwale et al 2017), and Boer, 2.0 kids/doe (Erasmus 2000). However, fecundity can be low with reports of 95% of does producing single kids (Aldomy et al 2009).…”
Section: Age Of Puberty Ovulation Rate and Fecunditymentioning
confidence: 99%
“…Ovulation rate sets the upper limit to fecundity (the number of kids born per pregnant doe). Goats are prolific breeders and high rates of fecundity have been reported in numerous countries and breeds, including in Kalahari Red, 1.6 kids/ doe (Oderinwale et al 2017), and Boer, 2.0 kids/doe (Erasmus 2000). However, fecundity can be low with reports of 95% of does producing single kids (Aldomy et al 2009).…”
Section: Age Of Puberty Ovulation Rate and Fecunditymentioning
confidence: 99%
“…In Nigeria, the WAD and RS goats are the most prolific breeds with average litter size of 1.60 and 1.45, respectively (Abubakar et al, 2013;Oga, 2016). Information based on limited data showed that mean litter size of KR goats bred in Nigeria was 1.67 for dams fed with grass supplemented with low protein diets (Oderinwale et al, 2017). Over the past decades, the application of traditional selective breeding to improve litter size resulted in limited success due to its low heritability (Otuma and Onu, 2013).…”
Section: Introductionmentioning
confidence: 99%